PAPILLARY PINEOCYTOMA IN CHILD: A CASE REPORT - Marcol, Wieslaw; Kotulska, Katarzyna; Grajkowska, Wieslawa; Golka, Dariusz; Wlaszczuk, Pawel; Drogosiewicz, Monika; Mandera, Marek; Lewin-Kowalik, Joanna; Roszkowski, Marcin (Biomedical papers, 2007)
Background: Papillary pineocytoma is an extremely rare tumor usually with a poor outcome.Case report: We report a case of a 10-year-old-girl with pineal gland tumor and obstructuve hydrocephalus diangnosed using MRI. The child was successful treated by insertion of a ventriculoperitoneal shunt and consecutive tumor resection by supracerebellar-infratentorial approach. Histopathological examination showed a papillary structure of the pineocytoma. As such, tumors are considered to be aggressive the child was subjected to radio- and chemotherapy.Conclusion: At six year follow-up after surgery, the patient is symptom-free and the MRI shows no tumor recurrence.
Keywords: Pineal tumors/Pineocytoma/Papillary structures/Prognosis/Therapy/